The effect of sponsorship portfolio size on brand choice: an experimental approach. Issue 10 (25th February 2021) - Breuer, Christoph; Dallmeyer, Sören; Rumpf, Christopher; Orlowski, Johannes
ABSTRACT: Profound knowledge of the behavioural response to sponsorship messages is sparse. In an effort to provide a better understanding of the relationship between sponsorship investments and the consumer's brand choice, an online experiment was conducted focusing on the role of the sponsorship portfolio size. In the context of sponsorship activities in the English Premier League, the study investigates how brand decision making can be influenced by the number of sponsored players wearing a particular footwear brand. Based on a microeconomic perspective, additional factors influencing the brand decision-making process, such as the overall brand status and prior brand experience, are considered. Logit regression models reveal that brand-choice behaviour is sensitive to the extent of sponsorship portfolio size, however, in a non-linear way. The results can be regarded as a next step in predicting the behavioural outcomes from sponsorship activities as the basis to estimate the economic efficiency of sponsorship investment.